IDENTIFYING TEACHERS’ AND STUDENTS’ NEEDS ON ZERO HUNGER-BASED BIG BOOK FOR SHARED READING ACTIVITIES - Gede Gunawan; Ni Wayan Surya Mahayanti; Luh Gd Rahayu Budiarta (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Creating shared reading experiences that sustain preschool children's behavioral engagement remains challenging when literacy media do not adequately accommodate children's visual needs or integrate sustainability values into meaningful learning contexts. This study was therefore conducted to identify the needs of teachers and preschool children as the foundation for developing a Big Book based on Zero Hunger (SDG 2) at Girikarnika Montessori Preschool. The research represents the needs analysis stage of a Design and Development (D&D) study and was carried out using a descriptive qualitative approach. Data were gathered through classroom observations, semi-structured interviews with two teachers, documentation, and field notes, and subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing, supported by source triangulation to enhance credibility. The findings revealed that children's sustained engagement during shared reading was influenced by the size of the reading media, the dominance of visual illustrations, the simplicity of the textual content, opportunities for interaction, and the relevance of the story to children's everyday experiences. Teachers also emphasized the need for instructional media featuring large illustrations, concise sentences, participatory learning activities, and narratives that promote healthy eating habits through collaborative partnerships between schools and families. These findings provide the conceptual foundation for developing the Nutritional-Literacy Shared Engagement Framework (NLSE-Framework) as a framework for designing literacy media that simultaneously strengthens early literacy, behavioral engagement, and sustainability values in early childhood education. ABSTRAK Kegiatan shared reading pada pendidikan anak usia dini belum sepenuhnya mampu mempertahankan behavioral engagement anak ketika media yang digunakan memiliki keterbatasan visual dan belum mengaitkan pengalaman membaca dengan nilai keberlanjutan. Situasi tersebut mendorong dilakukannya penelitian ini untuk memetakan kebutuhan guru dan anak prasekolah sebagai landasan pengembangan media Big Book berbasis Zero Hunger (SDG 2) di Girikarnika Montessori Preschool. Penelitian ini merupakan tahap analisis kebutuhan dalam penelitian Design and Development (D&D) yang dilaksanakan menggunakan pendekatan deskriptif kualitatif. Data diperoleh melalui observasi kelas, wawancara semi-structured terhadap dua guru, dokumentasi, dan catatan lapangan, kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña melalui proses kondensasi data, penyajian data, serta penarikan kesimpulan yang diperkuat dengan triangulasi sumber. Temuan memperlihatkan bahwa keberlangsungan keterlibatan anak selama shared reading dipengaruhi oleh ukuran media, dominasi ilustrasi, kesederhanaan teks, peluang berinteraksi, dan kedekatan isi cerita dengan pengalaman sehari-hari. Guru juga mengharapkan media yang menghadirkan ilustrasi berukuran besar, kalimat singkat, aktivitas partisipatif, serta narasi yang menanamkan kebiasaan makan sehat melalui kolaborasi sekolah dan keluarga. Keseluruhan temuan tersebut menjadi dasar konseptual bagi pengembangan Nutritional-Literacy Shared Engagement Framework (NLSE-Framework) sebagai acuan perancangan media literasi yang mengintegrasikan penguatan literasi awal, behavioral engagement, dan nilai keberlanjutan sejak usia dini.